Application of Social Media Technology in Digital Tourism Marketing: A Case Study of Instagram and TikTok Usage - M. Afriansyah; Valian Yoga Pudya Ardhana; Joni Saputra (Ali Institute of Reseach and Publication, 2025)
Bunut Baok Village in Central Lombok Regency offers a stunning tourist destination with beautiful natural views and waterfalls. However, the popularity of this tourist attraction is still low, both among local and foreign tourists, because it is not widely known. Researchers took the initiative to utilize social media platforms Instagram and TikTok as promotional tools to introduce the Bunut Baok Tourism Village. By creating official accounts on these two platforms, information regarding the tourist attractions of Bunut Baok Village can continue to be updated and accessed by a wider audience. Instagram and TikTok, with their various features and the newest trends, are very effective in assisting promotional activities. Through interesting and interactive content, user interest in Bunut Baok Tourism Village can be increased, thereby expanding the reach of promotions and attracting more visitors. This research uses the waterfall method and aims to examine the use of Instagram and TikTok as digital promotional strategies to increase the popularity and number of visits to Bunut Baok Tourism Village. It is hoped that the results of this research can make a real contribution to the development of local tourism by optimizing social media as an effective and efficient promotional tool.